Compliance Risk Assessment in the Banking Sector: Application of a Novel Pairwise Comparison-Based PRISM Method - Ferenc Bognár; Balázs Szentes; Petra Benedek (Complexity)
Up-to-date compliance management uses a risk-based approach based on international standards. In addition to techniques and practices, implementing compliance measures is determined by principles and culture. Compliance risk assessment is an evolving field in theory and practice. Compliance risk management is complex and highly dependent on the decisions of experts. This article presents a new compliance risk assessment method based on a commercial banking case study. In the study, the Guilford method is used to extend the Partial Risk Map (PRISM) assessment technique, and the steps of the proposed pairwise comparison-based PRISM method are described in detail. Since risk assessment is critical to the operation and development of compliance management systems, the proposed risk assessment method involves testing individual evaluations’ consistency and the results’ robustness. The best-fitting and outlier experts can be identified based on testing the impact of individual expert rankings on the aggregated ranking. The main finding is that top partial risks can be identified by applying the proposed pairwise comparison-based PRISM technique; therefore, possible optimal risk mitigation strategies and measures can be designed.